Mobile and Ubiquitous Systems: Computing, Networking, and Services 9th International Conference, MobiQuitous 2012, Beijing, China, December 12-14, 2012. Revised Selected Papers - Zheng, Kan.; Li, Mo.; Jiang, Hongbo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the 9th International ICST Conference on Mobile and Ubiquitous Systems: Computing, Networking, and Services, MobiQuitous 2012, held in Beijing, China, Denmark, in December 2012. The revised full papers presented were carefully reviewed and selected from numerous submissions. They cover a wide range of topics such as localization and tracking, search and discovery, classification and profiling, context awareness and architecture, location and activity recognition. The proceedings also include papers from the best paper session and the industry track, as well as poster and demo papers.
Traffic Density Estimation Protocol Using Vehicular Networks -- Mobile-to-Mobile Video Recommendation -- Dual Codes: Backward Compatible Multi-layer 2D-Barcodes -- A Collaborative Framework of Enabling Device Participation in Mobile Cloud Computing -- Design and Evaluation of a Publish/Subscribe Framework for Ubiquitous Systems -- Where am I? Using Mobile Sensor Data to Predict a User$1 (Bs Semantic Place with a Random Forest Algorithm -- Recognizing a Mobile Phone$1 (Bs Storing Position as a Context of a Device and a User -- Privacy Preserving Social Mobile Applications -- Fine-Grained Transportation Mode Recognition Using Mobile Phones and Foot Force Sensors.s
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer network architectures; Information storage and retrieval systems; Computer Science; Computer System Implementation; Information Storage and Retrieval; Computer Communication Networks; Special Purpose and Application-Based Systems; Computers and Society; Information Systems Applications (incl. Internet).